Spatial modelling of damage accumulation in bone cement - Heron, Elizabeth A. (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2005)
In this thesis we develop spatial models for damage accumulation in the bone cement of hip replacement specimens. A total hip replacement consists of an artificial cup, forming the socket portion of the joint, and a prosthesis inserted into the femur, replacing the ball part of the joint. Both components are fixated to the bone using an acrylic polymer known as bone cement. The dominant mode of failure of the hip replacement is the aseptic loosening of the components due to damage accumulation consisting of crack initiation and crack growth in the bone cement.
Keywords: Statistics, Ph.D.; Ph.D. Trinity College Dublin